2019
DOI: 10.1101/591164
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Chemical Probe of CARM1 Alters Epigenetic Plasticity against Breast Cancer Cell Invasion

Abstract: CARM1 is a cancer-relevant protein arginine methyltransferase that regulates many aspects of transcription. Its pharmacological inhibition is a promising anti-cancer strategy. Here SKI-73 is presented as a CARM1 chemical probe with pro-drug properties. SKI-73 can rapidly penetrate cell membranes and then be processed into active inhibitors, which are retained intracellularly with 10fold enrichment for days. These compounds were characterized for their potency, selectivity, modes of action, and on-target engage… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…2 D). (S)-SKI-72 was previously developed as a potent inhibitor of the protein arginine methyltransferase 4 (PRMT4) [ 24 ]. Compared to sinefungin and AdoHcy/AdoMet, ( S )-SKI-72 is further derivatised with an N -benzyl substituent at the 6′ position and substitution at the α-amino carboxylate moiety ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 D). (S)-SKI-72 was previously developed as a potent inhibitor of the protein arginine methyltransferase 4 (PRMT4) [ 24 ]. Compared to sinefungin and AdoHcy/AdoMet, ( S )-SKI-72 is further derivatised with an N -benzyl substituent at the 6′ position and substitution at the α-amino carboxylate moiety ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, since ( S )-SKI-72 exhibits poor membrane permeability [ 24 ], we examined the effect of its prodrug derivative (S)-SKI-73, in which the 9′-amine moiety is cloaked with the trimethyl-locked quinone butanoate moiety, on intact HEK293 cells. Previous observations have shown that once (S)-SKI-73 passes inside the cell membrane, it is metabolised into (S)-SKI-72 and 6′-N-benzyl-homosinefungin, which then accumulates inside the cell [ 24 ]. Following 12 or 48 h incubation of (S)-SKI-73 added to the media of HEK293 cells, assay of MTHFR activity from cell lysates revealed no effect on residual MTHFR activity regardless of the concentration of (S)-SKI-73 provided ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Keeping this substitution in designing future nsp14 inhibitors will provide selectivity against PKMTs. WZ16 39 and Compound 8 are PRMT4 (CARM1) inhibitors. Although Compound 8 is a relatively weak nsp14 inhibitor (IC 50 : 95 ± 6 μM) it is likely cell-permeable (US20180305391A1).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of reported PRMT4 inhibitors shows moderate to poor selectivity against other Type I PRMTs 16,17 and/or lack of cellular activity, 18–20 with the notable exceptions of PRMT4 selective chemical probes 1 and 2 reported by Structural Genomics Consortium 14,21 and Epizyme, 15 respectively. Here, we report the development of indole based, potent and PRMT4 selective inhibitors starting from a dual PRMT4/6 inhibitor scaffold.…”
Section: Figurementioning
confidence: 99%